The Ittifaq Movement among Russia’s Muslims in the beginning of the Twentieth Century: The ideas of ‘Abd Rashid Ibrahimov - Akhmetova, Elmira (2019)
This paper studies the development of intellectual and political thought of the Muslims of the Imperial Russia in the beginning of the twentieth century on the example of the ideas of Abd Rashid Ibrahimov (1857-1944).